Circular RNAs in diabetes mellitus and its complications - Fan, Wenqi; Pang, Haipeng; Xie, Zhiguo; Huang, Gan; Zhou, Zhiguang (Frontiers in Endocrinology, 2022)
Diabetes mellitus (DM) is an endocrine disorder characterized by a relative or absolute lack of insulin due to dysfunction or destruction of β-cells. As one of the fastest growing challenges to global health in the 21st century, DM places a tremendous burden on affected individuals and their families and countries. Although insulin and antidiabetic drugs have been applied in DM, a radical cure for the disease is unavailable. Presently, the pathogenesis of DM remains unclear. The emerging role of circular RNAs (circRNAs) in DM has become a global research issue. CircRNAs have been verified to participate in the onset and progression of DM, implying their potential as novel biomarkers and treatment tools. In this review, we briefly introduce the characteristics of circRNAs. Next, we will focus on the specific role of circRNAs in type 1 diabetes mellitus, type 2 diabetes mellitus, gestational diabetes mellitus and diabetes-associated complications separately.